Hemophagocytic lymphohistiocytosis-a rare life threatening association with scrub typhus: case report - Virk, Arashdeep; Singla, Mohit; Trivedi, Pranay; Bhattacharjee, Prasun; Tiwari, Abhinav (International Journal of Contemporary Pediatrics, 2024)
Scrub typhus is an important cause of acute febrile illness and one of the re-emerging infectious diseases in India particularly in southern Rajasthan. Hemophagocytic lympho-histiocytosis (HLH) results from an uncontrolled and ineffective hyperinflammatory response to a variety of triggers. HLH is further subdivided into primary and secondary type. We present a case of Scrub typhus which presented with multiple organ dysfunction syndrome (MODS) and secondary HLH which is a rare entity. A 9-month-old male child presented with high grade fever with encephalopathy. Examination showed hepatosplenomegaly, cervical Lymph adenopathy with eschar mark visible on abdomen. Scrub typhus was suspected on clinical grounds and further investigations were done. Serological diagnosis was strongly positive for scrub typhus. Initially, child did not respond to doxycycline, so further investigations were done to rule out HLH which fits into criteria of secondary HLH as per the revised HLH 2004 protocol. In view of secondary HLH and MODS methylprednisolone was added to treatment. Child responded to steroids and there was complete recovery. Scrub typhus patient with progressive MODS, in spite of appropriate antimicrobial therapy should raise the suspicion of secondary HLH which is rare but life-threatening condition and steroids plays an important role in the management of this condition.